Providing Counseling and Efforts to Overcome Hypertension in The Elderly Through a Medical Herbal Approach (Basil And Cucumber Jelly) - Silawati, Vivi; Azzahroh, Putri (International Journal of Community Services, 2024)
Based on 2018 Bogor City Health Service data, hypertension is included in the top ten most common diseases in Bogor City, to be precise, the second most common disease after acute nasopharyngitis. Hypertension visit data increased to 47,373 or 19% in 2018 (Bogor City Health Office, 2018). To provide education related to hypertension in the elderly, the benefits and methods of making basil and cucumber jelly and to help reduce blood pressure during the remaining years of old age, especially for elderly women during menopause. Providing direct counseling and action to the elderly. A total of 40 elderly people received counseling about hypertension and received basil and cucumber jelly. Cucumber basil jelly is very effective to give to the elderly in reducing and lowering blood pressure levels.